Bromodomain-peptide displacement assays for interactome mapping and inhibitor discovery. - Philpott, M; Yang, J; Tumber, T; Fedorov, O; Uttarkar, S; Filippakopoulos, P; Picaud, S; Keates, T; Felletar, I; Ciulli, A; Knapp, S; Heightman, T (2011)
Histone lysine acetylation is a key component of epigenetic regulation of gene transcription. Bromodomains, found in histone acetyl transferases and other chromatin-associated proteins, bind selectively to acetylated lysines, acting as "readers" of the histone code, and have recently been shown to contain a druggable binding pocket. Here we report the development of high-throughput assays that quantify the binding of bromodomains to acetylated histone peptides. We have used these assays to screen for histone binding partners of as yet uncharacterized bromodomains, adding to current knowledge of the histone code and expanding the repertoire of assays for chemical probe discovery. We have also demonstrated that these assays can be used to detect small molecule binding from the very weak to the nanomolar range. This assay methodology is thereby anticipated to provide the basis both for broader interactome profiling and for small molecule inhibitor discovery.